Design, synthesis and structure–activity relationship studies of novel sirtuin 2 (SIRT2) inhibitors with a benzamide skeleton. Issue 2 (15th January 2015) - Sakai, Taki; Matsumoto, Yotaro; Ishikawa, Minoru; Sugita, Kazuyuki; Hashimoto, Yuichi; Wakai, Nobuhiko; Kitao, Akio; Morishita, Era; Toyoshima, Chikashi; Hayashi, Tomoatsu; Akiyama, Tetsu
Graphical abstract